National Maritime Single Window – Cost-Benefit Analysis of Montenegro Case Study - Kapidani, Nexhat; Tijan, Edvard; Jović, Marija; Kočan, Enis (Promet - Traffic&Transportation, 2020)
In this paper, the costs and benefits of the National Maritime Single Window (NMSW) for coastal countries that have limited human resources and infrastructure related to maritime traffic are researched. A general method for conducting a cost-benefit analysis of NMSW implementation is proposed. Using this method and the input data for Montenegro, as an example of a small-sized coastal country, the authors assess whether such an investment in NMSW implementation can be beneficial to coastal countries with limited resources.